Interview with Joaquín García Roca (Journal of Parents and Teachers, 2014)
In this article, Joaquín García Roca answers some questions about his latest book, Jóvenes, Universidad y compromiso social: una experiencia de insercióncomunitaria. In this book a project of community insertion with roots in the university community is narrated, which began in 1994. The goal of the project was to try that the students knew a reality that a priori was strange and hidden to them. Following that experience guide your own life.
Keywords: social commitment; community insertion; reality; goals